2021
DOI: 10.1136/bjophthalmol-2020-318049
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-based surgical education for glaucoma versus conventional training alone: the GLAucoma Simulated Surgery (GLASS) trial. A multicentre, multicountry, randomised controlled, investigator-masked educational intervention efficacy trial in Kenya, South Africa, Tanzania, Uganda and Zimbabwe

Abstract: Background/AimGlaucoma accounts for 8% of global blindness and surgery remains an important treatment. We aimed to determine the impact of adding simulation-based surgical education for glaucoma.MethodsWe designed a randomised controlled, parallel-group trial. Those assessing outcomes were masked to group assignment. Fifty-one trainee ophthalmologists from six university training institutions in sub-Saharan Africa were enrolled by inclusion criteria of having performed no surgical trabeculectomies and were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 37 publications
0
25
0
1
Order By: Relevance
“…The trial was conducted between October 2017 and July 2019 (trial protocol available as online annex). 9 , 10 The details of the intensive glaucoma SBSE curriculum can be found in Appendix A . Trainees participating in the trial (from the intervention and control arms) were identified using purposeful sampling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The trial was conducted between October 2017 and July 2019 (trial protocol available as online annex). 9 , 10 The details of the intensive glaucoma SBSE curriculum can be found in Appendix A . Trainees participating in the trial (from the intervention and control arms) were identified using purposeful sampling.…”
Section: Methodsmentioning
confidence: 99%
“…The OLIMPICS and GLASS trials conducted by Dean et al between 2017 and 2019 examined the efficacy of intensive, high-fidelity surgical simulation training on cataract and glaucoma surgical competency in residents based in Eastern, Central and Southern Africa. 8 , 9 These trials demonstrated the superiority of SBSE in improving surgical competency compared to conventional training alone. Yet, whilst these results are promising, further research is needed to explore the acceptability of this newer educational method in ophthalmology, along with the perceived barriers to its implementation in sub-Saharan training institutions.…”
Section: Introductionmentioning
confidence: 98%
“…In a randomized, controlled, investigatorblinded multi-centre study Dean et al [39] aimed to evaluate if an intense 5-day simulation-based training course improved simulated glaucoma surgery (trabeculectomy) competence at 3 months as assessed on the Ophthalmic Simulation Surgical Competency Assessment Rubric (SIM-OSSCAR) by two masked graders. Synthetic simulation eyes were used (PS-OS-010, Philips Studio, Bristol, UK).…”
Section: Other Simulation-based Proceduresmentioning
confidence: 99%
“…Published reports in literature stress the importance of simulator-based training to facilitate the rapid acquisition of surgical skills and improve patient safety profiles. [ 16 17 ] The simulator consists of a model eye mounted on a mannequin head, which is connected to a microscope with a camera and a computer interface. Internal sensors are present to track the movements and positions of the surgical instruments, which produces a virtual image that is seen on both the microscope and the touch screen.…”
Section: Wet Lab Trainingmentioning
confidence: 99%